G Protein‐Gated Inwardly Rectifying Potassium Channel Subunit 3 Knock‐Out Mice Show Enhanced Ethanol Reward. (25th March 2016) - Tipps, Megan E.; Raybuck, Jonathan D.; Kozell, Laura B.; Lattal, K. Matthew; Buck, Kari J.
Abstract : Background: G protein‐gated inwardly rectifying potassium (GIRK) channels contribute to the effects of a number of drugs of abuse, including ethanol. However, the roles of individual subunits in the rewarding effects of ethanol are poorly understood. Methods: We compare conditioned place preference (CPP) in GIRK3 subunit knock‐out (GIRK3 −/− ), heterozygote (GIRK3 +/− ), and wild‐type (WT) mice. In addition, the development of locomotor tolerance/sensitization and the effects of EtOH intoxication on associative learning (fear conditioning) are also assessed. Results: Our data show significant EtOH CPP in GIRK3 −/− and GIRK3 +/− mice, but not in the WT littermates. In addition, we demonstrate that these effects are not due to differences in EtOH metabolism, the development of EtOH tolerance/sensitivity, or associative learning abilities. While there were no consistent genotype differences in the fear conditioning assay, our data do show a selective sensitization of the impairing effects of EtOH intoxication on contextual learning, but no effect on cued learning. Conclusions: These findings suggest that GIRK3 plays a role in EtOH reward. Furthermore, the selectivity of this effect suggests that GIRK channels could be an effective therapeutic target for the prevention and/or treatment of alcoholism. Abstract : GIRK channels are emerging as an important neural target of alcohol. Here, we investigate the role of the GIRK3 subunit in ethanol reward using conditioned place preference. Our results demonstrate that the loss of GIRK3 significantly enhances preference for the ethanol‐paired chamber after only four pairings. Further, we show that this effect is not due to the differences in ethanol metabolism, tolerance/sensitivity, or ethanol effects on associative learning. These data highlight the potential utility of GIRK‐targeted therapeutics in the treatment of alcoholism.